(untitled) (Medicine Today, 2017)
Vitiligo is an acquired, pigmentary skin disorder which is disfiguring and difficult to treat. Phototherapy and application of topical corticosteroids are most commonly prescribed. However, these therapies are often not effective and use of corticosteroids on the face may lead to cutaneous atrophy, telangiectasia, and ocular complications. This case control study was conducted among the patients who sought health care in the Dermatology and Venereology out patient department of Ibn Sina Medical College, Dhaka from January, 2014 to June, 2015. The study was conducted with a view to evaluate the efficacy of topical tacrolimus in localized vitiligo and to see the adverse effects of topical tacrolimus in the treatment of vitiligo. This study assessed the efficacy and safety of tacrolimus 0.03% ointment in patients with vitiligo compared with control. 60 patients were enrolled as case group, among them 22 were male and 38 were female. There mean age was 23.33 years with a standard deviation of ±11.43 years. Another 60 patients were enrolled as control group. Patients in case group were treated with tacrolimus 0.03% ointment applied twice daily. Monthly evaluations were performed. At six months, 50 patients (89%) achieved varying levels of repigmentation. There was a statistically significant decrease depigmentation & increase pigmentation at sixth month. Mean area of repigmentation was 33.33% with a standard deviation of ±23.90. 24 patients (40.0%) had reported up to 50% repigmentation. Sign and symptoms of erythema (10%) and burning (10%) were minimal. In conclusion, it is proposed that tacrolimus ointment may be a efficacious and safe option for the treatment of vitiligo. The ease of topical self-administration with minimal side effects makes this novel immunomodulatory agent a promising addition to the therapeutic armamentarium for vitiligo. Medicine Today 2017 Vol.29(1): 1-5